Visitor Perception Of The Tourist Experience In Kampuang Minang Nagari Sumpur Tourism Village - Sakira Putri Manurung; Habibatul Qolbi Sumardi; Lusia Oktaviani; Maria Dwi Sianipar; Alvian Maranalom Siregar; Kiki Rendhardi Napitupulu; Nina Novira; Eni Yuniastuti; Sendi Permana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Kampuang Minang Nagari Sumpur Tourism Village in South Batipuh District, Tanah Datar Regency, West Sumatra, is a cultural and natural tourism destination with the uniqueness of the gadang house that still functions as a residence, preserved Minangkabau traditions, and natural beauty such as Lake Singkarak. However, there is a gap between the expectations and reality of the tourist experience that visitors feel. This shows that even though the potential and attraction of tourism is huge, there are still weaknesses in destination management that can affect visitor perception and satisfaction. In addition, until now there have not been many studies that specifically examine the perception and experience of tourists in Kampuang Minang Nagari Tourism Village in Sumpur, even though visitor perception greatly determines the image, loyalty, and sustainability of tourist destinations. This study uses a quantitative descriptive approach with data collection techniques in the form of observations, questionnaires, and interviews with visitors. The data analysis technique uses a descriptive quantitative approach with the one score one indicator method based on the Likert Scale to identify visitors' perceptions of aspects of accessibility, facilities, tourist attractions, services, environmental conservation, and personal satisfaction and experience during travel. The results of the research are expected to provide a comprehensive overview as the basis for developing an effective and sustainable tourism village management strategy.